Synthesis of Some Mixed ligands Complexes of (2-hydroxy benzaldine)-4-amino Antipyrine and 1,10-phenanthroline and Studying their antibacterial activity - Baghdad Science Journal (مجلة بغداد للعلوم, 2017)
Complexes from the ligand (2-hydroxy benzaldine)-4-aminoantipyrine with some transition metal ions V(l?),Cr(lll),Fe(lll) and Co(ll) were prepared in the presence of the co-ligand 1,10-phenanthroline in alcoholic medium. These compounds were characterized by the available techniques: FT-IR ,UV-Visible ,magnetic susceptibility, Flame atomic absorption technique as well as elemental analysis and conductivity mesurments .From these spectral studies, a square pyramidal structure proposed for V(IV) complex and an octahedral geometry for Cr(III),Fe(III) and Co(II) complexes. The biological activity of the ligands and their complexes were evaluated by a gar plate diffusion technique against three human pathogenic bacterial strains: Pseudomonas aerogenuosa, E.schriachia coli. and Staphlococcus arureus. Some of the complexes were found to have a good antibacterial activity a gainst these pathogens.